The impact of vaccine hesitation on the intentions to get COVID-19 vaccines: The use of the health belief model and the theory of planned behavior model - Zeming Li; Ying Ji; Xinying Sun (Frontiers Media S.A., 2022)
ObjectDuring the later period of the COVID-19 pandemic, the public has been at risk of the evolving COVID-19 variants and hesitated to be vaccinated against COVID-19 to a certain extent. In this context, the health belief model (HBM) and the theory of planned behavior model (TPB) were used to compare and summarize the relationship between vaccine hesitation/non-hesitation and the intentions to get COVID-19 vaccines and its influencing factors.MethodsThe cross-sectional, population-based online survey was conducted from 14 April to 30 April 2021, and 1757 respondents were recruited to participate in the survey through the Wenjuanxing online survey platform. The HBM and TPB covariate scores were expressed using means and standard deviations and compared between groups using t-tests. Backward multiple linear regression models were used to explore the factors influencing the public's intentions to receive the COVID-19 vaccines.ResultsThis study found that educational background is one of the factors influencing vaccine hesitation. Most people with high education do not hesitate (65.24%), while a more significant proportion of people with low education have vaccine hesitation (66.00%). According to HBM, for the vaccine hesitation group, self-efficacy, family advice, and doctor's advice were the most critical factors affecting the public's future vaccination intentions; for the vaccine non-hesitation group, self-efficacy, doctor's advice, and perceived benefits are the most important influencing factors. According to the TPB, the subjective norm is the most critical factor affecting the future vaccination intention of the vaccine hesitation group, and the attitude toward behavior is the most critical factor affecting the future vaccination intention of the vaccine non-hesitation group.ConclusionsIn the context of COVID-19, the public's hesitation on the "current" vaccines will still affect future vaccination intentions. Using HBM and TPB would help health policymakers and healthcare providers formulate intervention plans.